The Design of Mold Clamping Mechanisms with Two Dead-Position Configurations - Chen, Tzu-Hsia; Hsieh, Long-Chang (Advances in Technology Innovation, 2020)
Blow-molding machines are divided into two types: (1) rotary type blow-molding machine, and (2) linear type blow-molding machine. Good kinematic characteristics of mold clamping mechanism is the goal pursued by manufacturers of blow-molding machine. Traditionally, the mold clamping mechanism has only one dead-position configuration for the mold in the closed position. When the mold is in the open position, the mold clamping mechanism does not have dead-position configuration. This study focuses on the design of mold clamping mechanisms with two dead-position configurations when the mold is in open and closed positions. Firstly, with reference to the existing patents, based on the Yan’s creative design methodology, four design concepts of mold clamping mechanisms are synthesized. Then, according to the studies on kinematics of mechanisms, three mold clamping mechanisms with two dead-position configurations are also synthesized. The results of this paper will enhance the research and development (R&D) capability of the mold clamping mechanisms to improve industrial competitiveness.